Barriers to visit restaurants by older adults in Malaysia - Ganesan, L.; Abu Bakar, Ainul Zakiah; Othman, Mohhidin; Haron, Sharifah Azizah (Academic Inspired Network, 2019)
The growth of older adults globally is inevitable as the by-product of medical technology advancement and lower fertility rate. Nevertheless, this age segment does not receive the attention they should as a consumer. While there are many studies done about restaurant preferences of older adults, the factors that stand as a barrier for the older segment to visit a restaurant were not given much importance. To fill the gap in the literature, this research will focus on identifying the barriers preventing older adults to visit a restaurant. Qualitative approach was used in this study. 15 informants aged 55 or above were chosen from Klang Valley using the purposive sampling method. The semi-structured interviews were recorded using a voice recorder. The obtained recordings were then transcribed, translated, coded, and analysed. Atlas.ti software (version 7) was used to help in the coding of the themes. Barriers identified in this research were cleanliness, service quality, ageing, life’s perspective and food. Recognising these barriers and improvising the restaurant marketing strategy based on it is expected to be beneficial.